PERBANDINGAN UJI DAYA HAMBAT ANTARA EKSTRAK AKAR BELUNTAS DENGAN KULIT BUAH MAHKOTA DEWA TERHADAP PERTUMBUHAN BAKTERI E.COLI - Agustina, Ika; Efrilia, Mega; Lisnawati, Nia (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2019)
When this has been much studied extracts of herbs or traditional medicines, among other crops beluntas (Pluchea indica Less) and mahkota dewa (Phaleria macrocarpa (Scheff.) Boerl.) As an antibacterial. Previous research has suggested that the rind of the gods crown and root beluntas known to have antibacterial activity, but please be more certain with the same methods and evaluation in testing the antibacterial activity of both plants against bacteria Escherichia coli. Are both these plants have a vigorous activity the same or different from one another. The method used to test the antibacterial activity is using the disc. The results showed beluntas root extract has inhibitory activity against Escherichia coli was higher than fruit skin extracts gods crown with a minimum concentration of 6%, while the fruit skin extracts crowns a new god looks at a concentration of 12%. Based on the paired t-test showed that there is a significant difference between the antibacterial activity of root extracts beluntas with fruit leather crown god.